Chemical‐induced aseptic meningitis as a result of intrathecal hydromorphone therapy: Case report - Sydney Willhite; Sangeeta Juloori (Clinical Case Reports, 2021)
Abstract Chemical meningitis, though rare, is a diagnosis of exclusion that must be considered in patients presenting with neurologic symptoms of undetermined cause. It is likely that any substance in contact with CSF can be the culprit.